1999
DOI: 10.1159/000014183
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bradykinin in Neonatal Hemodynamic Effects of ACE Inhibition

Abstract: Angiotensin-converting enzyme (ACE) inhibitors exert their effects by inhibiting angiotensin II (AII) production, but also by inhibiting bradykinin (BK) degradation. In order to clarify whether BK is involved in the systemic effects of ACE inhibition in the newborn period, we investigated the effect of perindoprilat (20 μg/kg i.v.) in newborn rabbits, with or without the blockade of BK β2-receptors (Hoe 140, 300 μg/kg s.c.). The bolus infusion of perindoprilat resulted in a marked fall in mean arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Addition of the NO synthase inhibitor N -nitro-L-arginine methyl ester to PD 123319 completely blunted the AII-mediated increases in cGMP without potentiation of PD 123319 inhibition by Nnitro-L-arginine methyl ester, suggesting that all of the cGMP production via AII stimulation of AT 2 could be accounted for by increased NO production (22). AT 2 stimulation is also directly linked to BK release (19,23). Studies in genetically engineered mice lacking AT 2 have confirmed the concept that AT 2 mediates a BK-NO-cGMP vasodilator cascade (18).…”
Section: Discussionmentioning
confidence: 98%
“…Addition of the NO synthase inhibitor N -nitro-L-arginine methyl ester to PD 123319 completely blunted the AII-mediated increases in cGMP without potentiation of PD 123319 inhibition by Nnitro-L-arginine methyl ester, suggesting that all of the cGMP production via AII stimulation of AT 2 could be accounted for by increased NO production (22). AT 2 stimulation is also directly linked to BK release (19,23). Studies in genetically engineered mice lacking AT 2 have confirmed the concept that AT 2 mediates a BK-NO-cGMP vasodilator cascade (18).…”
Section: Discussionmentioning
confidence: 98%